2020
DOI: 10.1002/jso.25840
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative frailty predicts adverse short‐term postoperative outcomes in patients treated with radical nephroureterectomy

Abstract: Background To investigate the effect of frailty on short‐term postoperative outcomes and total hospital charges (THCs) in patients with non‐metastatic upper urinary tract carcinoma, treated with radical nephroureterectomy (RNU). Methods Within the National Inpatient Sample (NIS) database we identified 11 258 RNU patients (2000‐2015). We used the Johns Hopkins frailty‐indicator to stratify patients according to frailty status. Time trends and multivariable logistic, Poisson and linear regression models were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…There is an increasing need for the establishment of widely accepted specific urologic oncology calculators to predict the association between frailty and postoperative complications. However, due to the current lack of such specific indexes the use of a combination of the most accurate calculators is recommended to predict and prevent postoperative complications associated with frailty 9,14,[21][22] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is an increasing need for the establishment of widely accepted specific urologic oncology calculators to predict the association between frailty and postoperative complications. However, due to the current lack of such specific indexes the use of a combination of the most accurate calculators is recommended to predict and prevent postoperative complications associated with frailty 9,14,[21][22] .…”
Section: Resultsmentioning
confidence: 99%
“…Frailty. Five phenotypic criteria: unintentional weight loss, exhaustion, low energy expenditure, low grip strength, and/or slowed walking speed 21 .…”
Section: Johns Hopkins Frailty Assessment Calculatormentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence varies between studies. Rosiello et al [ 11 ] in a large study found it to be 16% in a group undergoing radical nephroureterectomy. In the group undergoing radical cystectomy in the study of Michel et al [ 12 ] it was 7%, while in the study of Yao-Dan Liang et al [ 13 ] the prevalence in different surgical wards was 18.8% to 41.9%.…”
Section: Resultsmentioning
confidence: 99%